Metaphor and Ideology in the Business Press: The Case of the Endesa Takeover - Isabel Negro Alousque (Miscelánea: A Journal of English and American Studies, 2012)
Ideology is present in language (Fairclough 1989) and is embodied in a range of linguistic devices. Metaphor is one of such devices, as has been shown in recent research (Fairclough 1992; Dirven and Frank 2001). In this article we explore the metaphorical base of the Spanish and British journalistic discourse on a specific business issue —the Endesa takeover— and the way ideology operates. The empirical data for our survey have been drawn from two newspapers (El País, Financial Times) published over a period running from September 2005 to April 2007. Our main assumption is that metaphor has an ideological value which is manifested through the positive or negative axiologisation of the takeover.
Keywords: metaphor; ideology; conceptual domain; mapping; evaluation